Fear of Missing Out and Social Media Usage as Catalysts for Entrepreneurial Interest through Entrepreneurial Motivation - Zidny Ilma Hasan; Muhammad Aqshel Revinzky (CV. Sakura Digital Nusantara, 2025)
This study aims to analyze the effect of the Ear of Missing Out (FOMO) phenomenon and the social media usage on entrepreneurial interest through entrepreneurial motivation in students of the Faculty of Economics and Business, Universitas Padjadjaran. FOMO that develops in the digital era through social media can affect the way students view entrepreneurial opportunities, both positively and negatively. This study used a quantitative approach with Proportional Random Sampling technique, involving 112 respondents from various study programs at the Faculty of Economics and Business Universitas Padjadjaran. Data were collected using a digital-based closed questionnaire with a Likert scale, which was then analyzed using the SPSS version 23 application, through descriptive statistical analysis, classical assumption tests, and path analysis. The results of this study are expected to provide insight into the relationship between FOMO, social media, motivation, and entrepreneurial interest, and contribute to the development of strategies to increase entrepreneurial interest among students. It is expected that the results of this study can encourage students to be more active in entrepreneurship as agents of change, create new jobs, and have a positive impact on the local and national economy.